The Impact of Leadership Styles, Knowledge Management Process and Team Outcomes on Project Success: A Study Among Employees of Software Companies in Pakistan - Siddiqui, Aqeel Wahab (2023)
By applying the concept from Resource Based View (RBV) and Knowledge-Based View (KBV), this study aims to determine the impact of Leadership Styles, Team Outcomes, and Knowledge Management Processes on project success (PS) in the software companies of Pakistan. The main cause of project failure in Pakistan is poor leadership which is a vital factor behind project success. There is generally little empirical testing of the direct and indirect relationships between leadership styles and project success. Research has focused primarily on the effect of various leadership styles on individual knowledge management, team outcomes, and project success. Since no leader practices a single style of leadership. Current research has called for more research to clarify the process of effect on project success of leadership styles. Moreover, the mechanism through which the impact of leadership styles is translated onto project success is still weak and scarce. By studying the mediating variables between leadership styles and project success, the study will add to the literature. The data were collected from 350 project team professionals working in the IT sector of Pakistan. The study applied partial least squares structural equation modeling to validate the direct and mediating effect. The result indicated that Leadership Styles have a positive and significant impact on project success. Moreover, the result further validated that knowledge management processes mediate the relationship between Leadership Styles and project success. The study further confirmed the positive and significant role of Team performance between Leadership Styles and Project success, however, team communication, empowerment, and identity were found Insignificant between leadership styles and project success in software companies in Pakistan. The implications of this research in software companies in Pakistan can be significant. The research emphasizes the positive and significant impact of leadership styles on project success. By adopting effective leadership styles, software companies can enhance their chances of achieving successful project outcomes. This can result in higher client satisfaction, increased profitability, and a stronger reputation in the industry. Moreover, Software companies can focus on implementing robust knowledge management practices to facilitate the sharing, creation, and utilization of knowledge within project teams. This can lead to improved decision-making, faster problem-solving, and better project performance. software companies in Pakistan should not dismiss the importance of team communication, identity, and empowerment. Instead, they should explore how these factors can be effectively integrated into their project management practices to foster collaboration, motivation, and a sense of ownership within project teams. There is a dearth of an empirical investigation on the relationship between Leadership Styles and Project Success in developing republics context. This study makes a significant contribution to the field of IT project management by demonstrating that these five styles of leadership if a project manager follows impact Project success. This is one of the earliest studies that explore the inter-relationship among Leadership Styles, Knowledge Management processes, team outcomes, and Project Success.